Development of Humpback Grouper Fish (Chromileptes altivelis) Culture in Gebe Island, Central Halmahera, North Moluccas - Muhamad Tomi Saiful Insani; Ichsan Kadir; Nur Bambang Priyo Utomo; Ridwan Afandi; . Sulistiono; Thomas Nugroho; Mufti Murhum; Hardono Manan (Institut Pertanian Bogor, 2017)
Gebe Island as one of the islands in Central Halmahera of North Moluccas Province, has a high potential of fishery resources both for capture and aquaculture fisheries. This activity aimed to improve community skill to rear humpback grouper fish (Chromileptes altivelis ) in floating net at Umera and Umiyal Villages as community empowerment in the Gebe Island. The method of this activities were training and mentoring. Juvenile of the fish was from artificial breeding, and collected naturally from the sea around the Gebe Island. According to the observation of the activity, the community can rear the humpback grouper fish from 5 cm to 2025 cm total body length per individual for 12 months (Umera Village), and it was from 5 cm to 1015 cm total body length per individual for 10 months (Umiyal Village). The fish grew to be 300 g/ind (in December 2013), 500 g/ind (July 2014), and 600 g/ind (October 2014). The community has been able to harvest and sell the grouper fish collected from the sea, reared for 24 months in the floating net.